A Note on Optimality of Quantum Circuits over Metaplectic Basis - Bocharov, Alex (Quantum Information and Computation, 2018)
Metaplectic quantum basis is a universal multi-qutrit quantum basis, formed by the ternary Clifford group and the axial reflection gate R=|0⟩⟨0|+|1⟩⟨1|−|2⟩⟨2| . It is arguably, a ternary basis with the simplest geometry. Recently Cui, Kliuchnikov, Wang and the Author have proposed a compilation algorithm to approximate any two-level Householder reflection to precision ε by a metaplectic circuit of R -count at most Clog 3 (1/ε)+O(loglog1/ε) with C=8 . A new result in this note takes the constant down to C=5 for non-exceptional target reflections under a certain credible number-theoretical conjecture. The new method increases the chances of obtaining a truly optimal circuit but may not guarantee the true optimality. Efficient approximations of an important ternary quantum gate proposed by Howard, Campbell and others is also discussed. Apart from this, the note is mostly didactical: we demonstrate how to leverage Lenstra's integer geometry algorithm from 1983 for circuit synthesis.